Cost-effectiveness of hydrophilic-coated intermittent catheters compared with uncoated catheters in Canada: a public payer perspective. (3rd July 2018) - Welk, Blayne; Isaranuwatchai, Wanrudee; Krassioukov, Andrei; Husted Torp, Louise; Elterman, Dean
Abstract: Study design: A Markov model was used to analyze cost-effectiveness over a lifetime horizon. Objective: To investigate the cost-effectiveness of hydrophilic-coated intermittent catheters (HCICs) compared with uncoated catheters (UCs) among individuals with neurogenic bladder dysfunction (NB) due to spinal cord injury (SCI). Setting: A Canadian public payer perspective based on data from Ontario; including a scenario analysis from the societal perspective. Methods: A previously published Markov decision model was modified to compare the lifetime costs and quality-adjusted life years (QALYs) for the two interventions. Three renal function and three urinary tract infection (UTI) health states as well as other catheter-related events were included. Scenario analyses, including utility gain from compact catheter and phthalate free catheter use, were performed. Deterministic and probabilistic sensitivity analyses were conducted to evaluate the robustness of the model. Results: The model predicted that a 50-year-old patient with SCI would gain an additional 0.72 QALYs if HCICs were used instead of UCs at an incremental cost of $48, 016, leading to an incremental cost-effectiveness ratio (ICER) of $66, 634/QALY. Moreover, using HCICs could reduce the lifetime number of UTI events by 11%. From the societal perspective, HCICs cost less than UCs, while providing superior outcomes in terms of QALYs, life years gained (LYG), and UTIs. The cost per QALY further decreased when health-related quality-of-life (HRQoL) gains associated with compact HCICs or catheters not containing phthalates were included. Conclusion: In general, ICERs in the range of CAD$50–100, 000 could be considered cost-effective. The ICERs for the base case and sensitivity analyses suggest that HCICs could be cost-effective. From the societal perspective, HCICs were associated with potential cost savings in our model. The results suggest that reimbursement of HCICs should be considered in these settings.